2010
DOI: 10.3724/sp.j.1005.2010.00632
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of the unisex-determine gene <I>M</I> in cu-cumber

Abstract: Sex determination in plants has various mechanism; however, a single gene locus controlling unisexual expression is unique in the Cucurbitaceae plants, particularly cucumber (Cucumis sativus L.) and melon (Cucumis melo L.). In this study, with quantitative RT-PCR method, two sets of near-isogenic lines (NILs) were used to analyze the expression pattern of gene CsACS2 (GenBank accession number FJ529216). Additionally, chemical applications (AgNO3 and AVG) were used to investigate the effect of the plant endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Both of them were the policy of state intervention in production, but Wang Anshi's means of state intervention was innovative. He abandoned the mechanical method of "when you reduced the market price and when you increased the market price" [13] He chose to convert the grain storage of the regular warehouse and the wide benefit warehouse into the capital. To farmers and urban craftsmen at an interest rate of 20 percent.…”
Section: Reform Is the Organic Unity Of Carrying Forward The Past And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both of them were the policy of state intervention in production, but Wang Anshi's means of state intervention was innovative. He abandoned the mechanical method of "when you reduced the market price and when you increased the market price" [13] He chose to convert the grain storage of the regular warehouse and the wide benefit warehouse into the capital. To farmers and urban craftsmen at an interest rate of 20 percent.…”
Section: Reform Is the Organic Unity Of Carrying Forward The Past And...mentioning
confidence: 99%
“…The renewal History As A Mirror ChangBian recorded: "JingDeGuan ten thousand member, the emperor bestowed more than twenty thousand, and for flat screen, more than three thousand three hundred member states county magistrate, total twenty-four thousand." [3] The reason could not be separated from the political system and official selection system of the Song Dynasty. The highly autocratic centralized political system laid the foundation for redundant officials.…”
mentioning
confidence: 99%
“…Hyper mutation and Receptor editing describe its main character. In the study of clonal selection and static clonal selection, the algorithm was found only practice in static situation with its low adaptability and high requirement for the surrounding [8]. So Kim and Bentley [3,7] held up the dynamic clonal selection algorithm in 2002 which concentrated on Network Intrusion Detection System which is full of variation of dynamic environment.…”
Section: Introductionmentioning
confidence: 99%
“…When an affinity higher than the previous iteration of the affinity of the fish, instead of SumAffinity, updated fish collection. [8] Determine whether the conditions meet the iteration, if it does not satisfy then repeat (3-7) step, until it meets the conditions of the iteration. [9] Algorithm terminates and gets the new collection of the optimal detector.…”
mentioning
confidence: 99%